S16 Acquired immune responses to the seasonal trivalent influenza vaccination in COPD. (December 2018) - Staples, KJ; Williams, NP; Bonduelle, O; Hutton, AJ; Cellura, D; Combadiere, B; Wilkinson, TMA
Abstract : Background: Influenza A virus (IAV) is a major global public health burden, particularly in the elderly and those with underlying respiratory conditions such as COPD. Epidemiological data suggests that influenza vaccination protects against all-cause mortality in COPD patients. However recent work has called the efficacy of the vaccine in COPD into question, suggesting there is a defect in the ability of COPD patients to mount an adequate humoral response to influenza vaccination. Objectives: The aim of our study was to investigate mechanisms driving the acquired immune responses to the seasonal trivalent influenza vaccination (TIV), in COPD subjects and healthy controls Methods: 47 subjects were enrolled into the study; 23 COPD patients, 13 age-matched healthy control (HC –≥50) and 11 young healthy control subjects (YC –≤40). Serum and PBMC were isolated pre-TIV vaccination and at 7d, 28d and 6 months post vaccine for antibody titre, T cell and ELISpot analysis. Results: The antibody titre to each of the three strains of virus was significantly increased 7 d post-vaccine (p<0.001), peaking at 28 d post whilst beginning to wane 6 months post-vaccine. The kinetics of the vaccine response were similar between YH, HC and COPD patients and there was no significant difference in antibody titres between the groups 28 d post-vaccine. This increase in antibody titre was reflected by a significant increase in H1N1-specific CD4 +T helper cells in the cohort 28 d post-vaccine (p<0.01) but there was no significant difference in the fold-induction of specific CD4 +T cells at any time point between groups. As there were no disease-dependent differences we investigated if there was any association of these measures with age. H1N1 (r=−0.4253, p=0.0036) and Flu B (r=−0.344, p=0.0192) antibody titre at 28 d negatively correlated with age as did H1N1-specific CD4 +T helper cells (r=−0.4276, p=0.0034). Conclusions: These results suggest that age is the primary determinant of response to trivalent vaccine and that there is no defect in COPD per se . The yearly trivalent vaccine should therefore be continued as an adjunct to COPD disease management.